LAND HUSBANDRY : APLIKASI BIOCHAR JERAMI PADI DI BUDIDAYA WIJEN (SESAMUM INDICUM L.) UNTUK PENINGKATAN KUALITAS TANAH - Dyah Yuniwati, Eny (JURNAL AGRI-TEK, 2016)
Land Husbandry is one soil conservation technology using rice straw as a soil amendment material in the form of biochar, which serves as a source of organic material plays an important role in improving soil physical and chemical properties. The purpose of this study is the improvement of soil quality in the cultivation of sesame (sesamum indicum.L.) To improve soil quality in conservation technology and land husbandry. This research method using Random Design Group (RAK) with 3 repetitions. The experiment was conducted in Nganjuk, East Java, Indonesia from April to November 2015. The Treatmeny used (P1) single rows 50 cm x 25 cm (control group), (P2) single rows 60 cm x 25 cm + biochar 5 t / ha, (P3) double row 40/80 cm x 25 cm + biochar 5 t / ha, (P4) double row 50/80 cm x 25 cm biochar 7.5 t / ha, (P5) double row 40/100 cm x 25 cm + biochar 5 t / ha and (6 ) double row 50/100 cm x 25 cm + biochar 7.5 t / ha. The result showed that the use of biochar can improve the physical properties of soil, including soil bulk density, porosity, water holding ability (water retention) and the permeability of the soil. The addition of biochar with a dose of 5 tons / ha has been able to increase the soil bulk density of 1.20 g / cm3, and lead the ability to hold water to increases to 38.20%. Application ofbiochar also raised the pH, and macro nutrients (N, P, K, Ca, Mg) and KTK. The addition of biochar at a dose of 7.5 tons / ha increased the pH of 5.55 and KTK15.29 cmol / kg and macro nutrient uptake increased significantlyKeywords: Biochar Applicatioan, sesame cultivation, soil quality